2012
DOI: 10.1371/journal.pone.0050731
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Chronic Pseudomonas aeruginosa Airway Infections in Cystic Fibrosis

Abstract: Background/MethodsThe molecular epidemiology of the chronic airway infections with Pseudomonas aeruginosa in individuals with cystic fibrosis (CF) was investigated by cross-sectional analysis of bacterial isolates from 51 CF centers and by longitudinal analysis of serial isolates which had been collected at the CF centers Hanover and Copenhagen since the onset of airway colonization over 30 years.ResultsGenotyping revealed that the P. aeruginosa population in CF is dominated by a few ubiquitous clones. The fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 36 publications
2
75
0
Order By: Relevance
“…The MICs of POL7001 and comparators were determined against a panel of P. aeruginosa CF strains (Table 1). P. aeruginosa lineages from nine CF patients, longitudinally collected during a period of up to 16 years and comprising 17 "early," 6 "intermediate," and 17 "late" isolates, were included in the study (19). Clonal P. aeruginosa isolates of each lineage showed different phenotypes that changed during genetic adaptation in CF lung (10,20,21).…”
Section: Resultsmentioning
confidence: 99%
“…The MICs of POL7001 and comparators were determined against a panel of P. aeruginosa CF strains (Table 1). P. aeruginosa lineages from nine CF patients, longitudinally collected during a period of up to 16 years and comprising 17 "early," 6 "intermediate," and 17 "late" isolates, were included in the study (19). Clonal P. aeruginosa isolates of each lineage showed different phenotypes that changed during genetic adaptation in CF lung (10,20,21).…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with the literature (36), and they highlight the fact that chronic infections are due to P. aeruginosa strains derived from various environmental reservoirs (37). Cramer et al (38) revealed in their study that there are 20 ubiquitous clones frequently found and that, for the CF population, the five most commonly isolated clones belong to these 20 clones.…”
Section: Discussionmentioning
confidence: 97%
“…In the German collection, higher resistance is essentially related to the presence of more sporadic MDR clones than in the two other countries. We cannot exclude differences in therapeutic management of patients among these three centers that may influence resistance selection (48), but this specific aspect was not within the scope of our study.…”
Section: Discussionmentioning
confidence: 99%